Handling Sports Injuries using the PEACE Method and Nutritional Management of Athletes After Sports Injuries - Mega Widya Putri; Gilang Nuari Panggraita; Lukman Alfaris (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service implementation aims to provide understanding to athletes and coaches in Pekalongan Regency regarding how to treat sports injuries using the PEACE method and nutritional management of athletes after sports injuries. In this way, it is hoped that coaches and trainers can handle the problems of middle-aged athletes when training and taking part in competitions so that athletes' achievements, especially in Pekalongan Regency, can be maximized. A coach must of course know how to organize nutrition for his athletes during pre-competition, competition and after competition, especially after it is discovered that the athlete has suffered an injury. This is done to maintain the athlete's performance while taking part in the event. The problem in Pekalongan Regency is that there are still many athletes and coaches who do not know how to treat sports injuries using the PEACE method and nutritional management after sports injuries. The reason is that so far there is only one trainer in Pekalongan Regency, who doubles as a technical, mental trainer and nutritionist. Seeing this problem, it is necessary to provide understanding to athletes and coaches regarding injury management and nutritional management for athletes. In carrying out this service, reflection, lecture, practice and discussion methods are used. This service activity went smoothly, respondents were enthusiastic about taking part in this activity. After respondents were given an explanation and understanding regarding handling sports injuries and nutritional management, they carried out a PEACE method practicum and created a nutrition program for athletes after sports injuries.